2004
DOI: 10.1039/b315693a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and molecular structure of Re(iii) 2-oxacyclocarbenes stabilised by a benzoyldiazenido ligand

Abstract: A family of new Fischer-type rhenium(III) benzoyldiazenido-2-oxacyclocarbenes of formula [(ReCl2[eta1-N2C(O)Ph][=C(CH2)nCH(R)O](PPh3)2][n = 2, R = H (2), R = Me (3); n = 3, R = H (4), R = Me (5)] have been prepared by reaction of [ReCl2[eta2-N2C(Ph)O](PPh3)2] (1) with omega-alkynols, such as 3-butyn-1-ol, 4-pentyn-1-ol, 4-pentyn-2-ol, 5-hexyn-2-ol in refluxing THF. The correct formulation of the carbene derivatives 2-5 has been unambiguously determined in solution by NMR analysis and confirmed for compounds 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The bond length between C1-C6 [1.351 (4) Å ] is the shortest among all the bond lengths in the phenyl group, possibly due to the inductive effect of fluorine. The spatial distance between the extreme atoms of propargylamine groups (C7Á Á ÁN1) was observed to be 3.508 (3) Å , which is slightly longer than for the other reported propargylamines (3.372-3.478 Å ; Marvelli et al, 2004;Sidorov et al, 1999Sidorov et al, , 2000, and possibly due to the open L-shaped structure of the molecule. Also, the piperazine ring is shown in its most stable chair form conformation in Fig.…”
Section: Structural Commentarymentioning
confidence: 65%
“…The bond length between C1-C6 [1.351 (4) Å ] is the shortest among all the bond lengths in the phenyl group, possibly due to the inductive effect of fluorine. The spatial distance between the extreme atoms of propargylamine groups (C7Á Á ÁN1) was observed to be 3.508 (3) Å , which is slightly longer than for the other reported propargylamines (3.372-3.478 Å ; Marvelli et al, 2004;Sidorov et al, 1999Sidorov et al, , 2000, and possibly due to the open L-shaped structure of the molecule. Also, the piperazine ring is shown in its most stable chair form conformation in Fig.…”
Section: Structural Commentarymentioning
confidence: 65%
“…In many “push–pull” alkenes, however, the interconversion barrier can be significantly lowered. Similarly, low barriers were observed for N=N bond rotation in Re complexes 121 a / b (Scheme ) …”
Section: Isomerisations and Rearrangementsmentioning
confidence: 73%
“…Similarly, low barriers were observed for N=Nb ond rotation in Re complexes 121 a/b (Scheme 38). [193] Bain and co-workers showed that in the crotonate 122 [194] rotation aboutt he nominally double bond has only 11-12 kcal mol À1 barrier whereas degenerate rotation of Me 2 NinE-122 requires 12-16 kcal mol À1 owing to entropye ffects and dipole moments of the ground and transition states. Ad ifferent dissociative mechanism of spontaneous Z/E interconversion of nitrosopyridine 123 was observed by Orrell's group.…”
Section: Cis-trans Isomerisationmentioning
confidence: 99%
“…Even Re(III) Fischer carbenes are rare; however, the one report we found characterized four Re(III)-Fischer carbene complexes with bond distances ranging from 1.990-2.021 Å. 15 In 1 2+ , the rhenium-carbene bond distance (Re6-C1) is 2.248 (16) Å. This longer bond length indicates a weaker interaction with the metal center.…”
mentioning
confidence: 74%